Chłopcy nazwani pueri w inskrypcjach chrześcijańskich Rzymu - Stawoska-Jundziłł, Bożena (Vox Patrum, 2008)
The paper relates to the information contained in the Early Christian inscriptions from Rome (IC V R v. 1 - 1 0 ), from the fourth to sixth century, concerning boys below 8 years of age and referred to in the epitaphs by the term puer. The age was selected so that the information concerned children and not teenagers when the overtone of such expression could have sexual connotations. There are only 38 such epitaphs for 1962 children in the above mentioned age (1.9% ). More than a half of them (20) are very modest containing only name, age and sometimes the simplest epithet and motto (bm, in pace). The rest however include the information typical of other children’s epitaphs, posthumous descriptions, baptism details and allusions to the social background. The founders of the tomb stones are parents (10) and then the term puer is additional, even tender but also anonymous people (28) when the term could signify a slave (only one sure case) or a foster child, a boy who knew the faith (puer in fide). In my opinion they must have been orphans brought up by the community, sometimes assigned to serve in the Church (especially boys called puer nomine X ).